Prawa osób pozbawionych wolności (skazanych i tymczasowo aresztowanych): [The rights of persons deprived of liberty] (Studia Prawnicze / The Legal Studies, 1986)
Among different concepts and aspects of human rights the status of the prisoner's rights has a quite special character. Because of his specific situation, some of his general rights are limited by the decision of competent State organs, and he is deprived of the right to liberty, in its large sense, for the period of his imprisonment. The author endeavours to determine the scope of these limitations, and to demonstrate that what is not embraced by the limitations and deprivation constitutes the right of the prisoner as a human being and citizen.The difficulties involved in winning recognition of the prisoner's rights are - due, inter alia, to a widerspread biased social attitude toward persons stigmatized ascriminals, to the authoritarian tendencies manifested by correctional functionaries in the manner in which they exercise their duties, all in all  - to a phenomenon which can be called "syndrom of slavery".The author sees the chance of a batter realisation of these rights in winning the consensus of the international community to the fundamental principles in this field. Consequently, he devotes much attention to an important document of the United Nations - the Standard Minimum Rules for the Treatment of Prisoners, and maintains that these Rules have gained the rank of the customary international law. Emphasizing their importance for inspiring the policies of States to the benetif of prisoners and as model for other Rules (for instance those adopted by the Council of Europe), the author raises the following objection: The UN Rules, instead of employing the phrase "the prisoner has the right to..." describe the tasks and obligations which should be accomplished towards prisoners by the penitentiary administration. To employ such formula is certainly not the same as to establish rights which can be implemented by the prisoner himself (enforceable rights).The author devotes also much attention to the prisoners' rights in Poland and, on the other side, considers the United States as a country which possesses a particularly large amount 'of material for reflections on penitentiary problems.The following conclusions are closing the article:• The attitude toward persons deprived of liberty should be freed of residues of the slavery syndrom which still linger in societies and in many penologists'• The prisoners' status should be based on a completely clear concept of his• A free, legally guaranteed and effective access to the courts constitutes the most valuable means of making these rights enforceable.• The contact with the outside world, organisations and social volunteers, granted liberally to prisoners should constitute one of their most important rights fostering also the rehabilitating aims